Genetic analysis of conformation traits in Icelandic horses with focus on head morphology and body length - Felt, Veronica (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2016)
In the breeding evaluation of Icelandic horses there are eight breeding goals that refer to conformation, for example head carriage. Genetic evaluation of the horse is an important part for succeeding with breeding goals and this information is taken from assessments from breeding field tests, including conformation of the horses. These assessments can then be used for retrieving an estimated breeding value (EBV) through Best Linear Unbiased Prediction method (BLUP) with a multivariate animal model. With this in mind a Genome-Wide Association Study (GWAS) was done, primarily focus set on the follow-up of results from previous studies (Shrestha et al. unpublished; Wellbring 2011) and the same material was used as the previous study used, horse owner information and genotypes as well as head morphology and body length as phenotypes. However, one distinct difference was made for this study, this time direct measurements were used instead of EBV´s when using the traits head morphology and body length. Direct measurements give more accuracy than EBV´s as traits within association studies. Direct phenotypes were collected with a questionnaire which was sent out to the 178 Icelandic horse owners. To further follow up the results from the previous study, a secondary study was done through t-tests. For the GWAS analysis, chosen phenotypes from the questionnaire were picked out and the results gave significant associations to the following phenotypes: appearance of jaws, muzzle circumference, jawbone circumference and head length) and one borderline significant association (height at withers). From the secondary study one significant p-value was obtained when comparing means for measurements on genotype GG/AA in the t-test for group 1 (body length: Chromosome 1). The significant p-value was 0.007 and where the mean also was 143.213.